2020
DOI: 10.32739/etkilesim.2020.5.92
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ‘WhatsApp’ for Collaborative Learning among Undergraduates

Abstract: The adoption of new media technologies is rapidly becoming a trend in educational environment. Given the growing popularity of social media, it has become pertinent to understand and adopt social media networks in developing future educational blue prints. This study investigates the extent to which WhatsApp platform could engender collaborative learning among undergraduate students in the University of Abuja, Gwagwalada, Nigeria. To achieve this aim, a dual research methodology was employed to drive the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…This leads to better understanding and also by putting effort into learning, students benefit more from the knowledge and gain the ability to express their opinions. The data available to us indicate that WhatsApp use by undergraduate students and youth is widespread that almost every student uses daily, this is especially valid in Africa, India, and the Middle East (Batra, 2016; Maniar & Modi, 2013; Pindayi, 2017; Udenze & Oshionebo, 2020). Tackling active learning through the use of this application should be quite an easy task for students.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This leads to better understanding and also by putting effort into learning, students benefit more from the knowledge and gain the ability to express their opinions. The data available to us indicate that WhatsApp use by undergraduate students and youth is widespread that almost every student uses daily, this is especially valid in Africa, India, and the Middle East (Batra, 2016; Maniar & Modi, 2013; Pindayi, 2017; Udenze & Oshionebo, 2020). Tackling active learning through the use of this application should be quite an easy task for students.…”
mentioning
confidence: 88%
“…Using WhatsApp for collaborative group assignments is not new and students in the region are already familiar with the use of WhatsApp groups to collaborate on their assignments (Lam, 2015; Matassi et al., 2019; Mazana, 2018; Udenze & Oshionebo, 2020). The researcher has observed that students in his classes are already using WhatsApp heavily in their daily communications and to collaborate unofficially on group assignments, so making the use of WhatsApp official and part of the requirement of the assignment was not a big leap.…”
mentioning
confidence: 99%
“…Researchers have also investigated the potential of formal AIMGs to encourage and enhance collaborative learning among students (e.g., Barhoumi 2015 ; Nitza & Roman 2016 ; Ntinda & Bidwell 2018 ; Basitere et al, 2019 ; Udenze & Oshionebo 2020 ). Across these studies results indicate that students are both willing and able to utilise formal AIMGs to share knowledge and engage in collaborative problem solving, particularly when they enjoy some degree of anonymity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prominent among these is the rise in staff workload that results from the increased volume of interactions and the expectation to be available for interaction at all times (Bouhnik & Deshen, 2014 ; Zulkanain et al, 2020 ). The high volume of messages from both staff and students also creates an increased possibility of the distribution of false information, confusion and misinterpretations of statements (Willemse, 2015 ; Zulkanain et al, 2020 ; Udenze & Oshionebo, 2020 ). In contexts where not all students enjoy equal access to devices and Internet connectivity, a formal AIMG may lead to information asymmetry (Willemse, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation